2018
DOI: 10.1088/1361-6528/aad9e8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of pristine and defective carbon–phosphide monolayers: a density functional tight-binding study

Abstract: Using density functional tight-binding theory, we investigated the elastic properties and deformation and failure behaviors of pristine and defective carbon-phosphide (CP) monolayers subjected to uniform uniaxial tensile strain along arm-chair (AC) and zig-zag (ZZ) directions. Two variants of CP (α-CP and β-CP) were studied and two types of carbon and phosphorous vacancies (single and double) were considered. It was found that carbon monovacancies have the lowest formation energy, while phosphorous divacancies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Beyond uniaxial tension, computational studies offer the flexibility to investigate deformation modes that are difficult to probe directly by experiments. For instance, several studies report the bending [91][92][93] and in-plane shear [94,95] responses of 2D materials. Furthermore, atomistic studies have also revealed exotic mechanical behaviors such as negative Poisson's ratios.…”
Section: Micro-brillouin Light Scattering (Bls)mentioning
confidence: 99%
“…Beyond uniaxial tension, computational studies offer the flexibility to investigate deformation modes that are difficult to probe directly by experiments. For instance, several studies report the bending [91][92][93] and in-plane shear [94,95] responses of 2D materials. Furthermore, atomistic studies have also revealed exotic mechanical behaviors such as negative Poisson's ratios.…”
Section: Micro-brillouin Light Scattering (Bls)mentioning
confidence: 99%